Corporate Governance, Executive Directors and Level of Voluntary Disclosure: The Case of Public Listed Companies in Thailand (Malaysian Management Journal, 2008)
This paper extends the literature on voluntary disclosure by reference to a developing country, namely Thailand, through a study of 70 voluntary disclosure items in the corporate annual reports of 317 public listed companies in 2004. The study examined the relationship between the level of voluntary disclosure and a single characteristic of corporate governance characteristics, namely the quality of the board of directors. It further examined the influence of the executive directors on this relationship. The findings suggested that the quality of the board of directors is positively associated with the level of voluntary disclosure, and this association appears to be weaker for firms with an executive director that has the family member, largest shareholder involved compared to the non-family member, largest shareholder and a high concentration of executive directors’ ownership compared to a low concentration of executive directors’ ownership. This effect is further exacerbated when board of directors’ quality levels increase. It was found that an executive director that has the family member, largest shareholder involved, and a high concentration of executive directors’ ownership are quasi moderators, which means they are both an independent and a moderating variable. As control variables, size of company, auditor type, and earnings return were found to have a significant influence on the level of voluntary disclosure. These results have important implications for good corporate governance policy formulation.